European UNESCO Geoparks: Introduction to Part I - Michael Benton (Geoconservation Research)
The concept of the volume is to survey all the key geoparks throughout Europe in terms of their palaeontological significance. The first 25 articles in this Part cover the long span of geological time from the Precambrian to the Permian, arranged in chronostratigraphic order. These document some of the most important early stages in the history of life, from its origin to the devastation end-Permian mass extinction.